Hybrid organic–inorganic supramolecular systems based on a pyridine end-decorated molybdenum(ii) halide cluster and zinc(ii) porphyrinate. Issue 5 (16th January 2019) - Volostnykh, Marina V.; Mikhaylov, Maxim A.; Sinelshchikova, Anna A.; Kirakosyan, Gayane A.; Martynov, Alexander G.; Grigoriev, Mikhail S.; Piryazev, Dmitry A.; Tsivadze, Aslan Yu.; Sokolov, Maxim N.; Gorbunova, Yulia G.
Abstract : Herein, first examples of supramolecular coordination bonded hybrids of Mo(ii ) cluster and zinc(ii ) porphyrinates are reported. Abstract : Herein, first examples of supramolecular hybrid organic–inorganic cluster-porphyrin [CP n ( n = 2, 6)] systems constructed via metal–ligand coordination have been reported. The pyridine end-decorated Mo(ii ) halide cluster ((Bu4 N)2 [Mo6 I8 (OOC-C5 H4 N)6 ]), possessing remarkable photophysical properties, was chosen as the inorganic part and A2 -type zinc porphyrin 5, 15-bis[( p -tolyl)porphyrinato(2-)]zinc was selected as the organic part. The crystal structures ofCP2 andCP6 hybrids have been characterised by single crystal X-ray diffraction. TheCP2 complex is composed of two zinc porphyrins, coordinated to pyridyl moieties of the same cluster molecule, related by an inversion center. In the case of theCP6 complex, each cluster has three pairs of coordinated symmetrically equivalent zinc porphyrins. Also, the formation of supramolecular hybridCP n ( n = 2, 6) systems was unambiguously demonstrated in solution via NMR and UV-Vis spectroscopy titration and diffusion ordered NMR spectroscopy (DOSY).